2018
DOI: 10.1021/acssynbio.7b00448
|View full text |Cite
|
Sign up to set email alerts
|

High GC Content Cas9-Mediated Genome-Editing and Biosynthetic Gene Cluster Activation in Saccharopolyspora erythraea

Abstract: The overexpression of bacterial secondary metabolite biosynthetic enzymes is the basis for industrial overproducing strains. Genome editing tools can be used to further improve gene expression and yield. Saccharopolyspora erythraea produces erythromycin, which has extensive clinical applications. In this study, the CRISPR-Cas9 system was used to edit genes in the S. erythraea genome. A temperature-sensitive plasmid containing the PermE promoter, to drive Cas9 expression, and the Pj23119 and PkasO promoters, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 58 publications
2
29
0
Order By: Relevance
“…In addition to verify that the GC content between 40% and 60% is favored for knockdown of a target gene, SOCS1 (suppressor of cytokine signaling 1), by sgRNA, this study also revealed that the positive traits in sgRNAs are the circumvention of both a C at position 3 and a G at position 16 (Bruegmann et al, 2019). Besides, the study of CRISPR/Cas9-mediated mutagenesis in Drosophila revealed that sgRNAs with four GC in the sequence of the six base pairs adjacent to the PAM sequence are severely favored (Liu et al, 2018). Further, Fu et al (2017) determined the efficacy of thousands of targets, applying this to the Escherichia coli type I-E Cascade (CRISPR-associated complex for antiviral defense) system.…”
Section: Gc Contentsupporting
confidence: 52%
“…In addition to verify that the GC content between 40% and 60% is favored for knockdown of a target gene, SOCS1 (suppressor of cytokine signaling 1), by sgRNA, this study also revealed that the positive traits in sgRNAs are the circumvention of both a C at position 3 and a G at position 16 (Bruegmann et al, 2019). Besides, the study of CRISPR/Cas9-mediated mutagenesis in Drosophila revealed that sgRNAs with four GC in the sequence of the six base pairs adjacent to the PAM sequence are severely favored (Liu et al, 2018). Further, Fu et al (2017) determined the efficacy of thousands of targets, applying this to the Escherichia coli type I-E Cascade (CRISPR-associated complex for antiviral defense) system.…”
Section: Gc Contentsupporting
confidence: 52%
“…Beyond genome editing, multiplexing with orthogonal catalytically inactive Cas proteins with different PAM specificities may allow transcriptional control of different gene subsets in actinomycetes using CRISPR interference (Rock et al, ; Tong et al, ; Zhao et al, ). Last but not least, we expect this expanded Cas toolbox to be relevant to the engineering of rare actinomycetes (Cohen & Townsend, ; Liu, Wei, & Ye, ; Wolf et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These data revealed that the genomes encode several biosynthetic gene clusters (BGCs) for the production of diverse secondary metabolites. However, only a few of the BGCs are expressed at standard laboratory conditions and, therefore, the biosynthetic potential of many actinomycetes remains unexploited [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Numerous strategies were developed to induce the expression of the BGCs and access the corresponding products.…”
Section: Introductionmentioning
confidence: 99%